The effects of fibrin and fibrin‐agarose on the extracellular matrix profile of bioengineered oral mucosa. (3rd November 2011) - Martin, S. San; Alaminos, M.; Zorn, T. M. T.; Sánchez‐Quevedo, M. C.; Garzón, I.; Rodriguez, I. A.; Campos, A.
Abstract Several studies have developed efficient oral mucosa constructs using different types of scaffold. However, the changes in the morphology and gene and protein expression profile that could occur in these artificial constructs remain unknown. This study compared the histology and expression of several extracellular matrix molecules in human artificial oral mucosa developed using two different types of scaffolds: fibrin and fibrin‐agarose. To that end, bioengineered oral mucosa stromas were constructed from biopsy samples of human oral mucosa and the substitute generated was analyzed at different periods of time in culture. Histological analysis was carried out by light and transmission electron microscopy and the expression of collagen types I, III, and VI, the proteoglycans decorin and biglycan, and the different chains of laminin, were assessed by immunoperoxidase technique. This study found that fibrin scaffolds accelerated fibroblast growth and remodeling of the scaffold, thus enhancing collagen fibrillogenesis. In the fibrin‐agarose scaffold, the morphology and organization of the fibroblasts did not change during the culture period. All extracellular matrix proteins analyzed were expressed in both scaffolds. However, in fibrin scaffolds, these proteins were widely distributed and replaced the scaffold during the follow‐up period. These results show that the substitutes generated showed histological and molecular similarities with native human oral mucosa stroma. In addition, it was observed that the nature of the biomaterial influenced the behaviour of the oral stromal fibroblasts, thereby modulating their growth, protein synthesis, and collagen fibrillogenesis. Copyright © 2011 John Wiley & Sons, Ltd.